1991
DOI: 10.1002/em.2850180414
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei as an index of cytogenetic damage: Past, present, and future

Abstract: The workshop was designed to present what is known about the production of micronuclei, what protocols are now accepted or proposed internationally, what new results have been obtained, and what new methods and protocols are likely to be forthcoming. This report is designed to convey the flavour of the workshop and to provide the essence of the new information. After the workshop an effort was made to determine what single protocol would satisfy the requirements set for the micronucleus test by as many regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
202
2
21

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(232 citation statements)
references
References 13 publications
4
202
2
21
Order By: Relevance
“…Micronuclei (MN) are well-characterized biomarkers of structural or numerical chromosomal damage; they arise from acentric chromosome fragments or lagging whole chromosome(s) that fail to incorporate into daughter nuclei after nuclear division (Heddle et al, 1991), and they are commonly evaluated in lymphocytes and erythrocytes, due to the ease of obtaining blood samples. Prompted by the observations of increased frequencies of micronucleated reticulocytes (MN-RET) in mouse pups exposed to ZDV, we designed a pilot study to determine if similar effects were detectable in human infants exposed to ZDV in utero and postnatally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronuclei (MN) are well-characterized biomarkers of structural or numerical chromosomal damage; they arise from acentric chromosome fragments or lagging whole chromosome(s) that fail to incorporate into daughter nuclei after nuclear division (Heddle et al, 1991), and they are commonly evaluated in lymphocytes and erythrocytes, due to the ease of obtaining blood samples. Prompted by the observations of increased frequencies of micronucleated reticulocytes (MN-RET) in mouse pups exposed to ZDV, we designed a pilot study to determine if similar effects were detectable in human infants exposed to ZDV in utero and postnatally.…”
Section: Introductionmentioning
confidence: 99%
“…We used a recently developed single-laser three-color flow cytometric system for enumerating MN-RET in human blood (Dertinger et al, 2004). The advent of this new technology was important for our study design because, although the mouse peripheral blood erythrocyte micronucleus test has been used routinely for decades to evaluate genotoxicity (Heddle et al, 1991;OECD, 1997;MacGregor et al, 1990;Albertini et al, 2000;Witt et al, 2000;Hayashi et al, 1994), there has not been a corresponding human assay because the human spleen, unlike the mouse spleen, rapidly removes damaged erythrocytes from circulation. Thus, until recently, experimental evidence of genotoxicity obtained through use of routine rodent erythrocyte MN studies could not be confirmed in the same cell type in humans unless the human subject had undergone splenectomy (MacGregor et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…El mecanismo mediante el cual pueden formarse micro-núcleos espontáneamente es por perdida mitótica de fragmentos acéntricos, donde cualquier fragmento cromosómico que no posea centrómero no podrá integrarse a un núcleo, durante la división celular, pues carece del elemento que le permita orientarse en el huso acromático. Estos elementos quedan rezagados y permanecerán en el citoplasma conformando uno o varios núcleos muy pequeños, que son los denominados micronúcleos (Heddle et al, 1991;Martínez, 2005).…”
Section: Resultados Y Discusiónunclassified
“…23 Clastogenic and aneugenic agents are known to affect the spindle apparatus, and can be differentiated on the basis of the relative induced micronucleus sizes or in the presence of kinetochores. 24,25 It is evident that micronuclei originating from chromosomal fragments are generally ought to be smaller than those resulting from whole chromosome(s). Due to aneugenic effect, bigger MNi are formed from the damage to the spindle apparatus of the cell resulting in the exclusion of whole chromosome, whereas clastogenic effect leads to the formation of smaller MNi from structural aberrations causing fragments of chromosomes.…”
Section: Discussionmentioning
confidence: 99%